Kebijakan Maritim dan Transformasi Industry Pelayaran Indonesia dalam Kerangka Penerapan Asas Cabotage - Febiyansah, Panky Tri (Pusat Penelitian Ekonomi-LIPI, 2010)
This paper studies the condition of domestic shipping transport in Indonesia. From the viewpoint of participating in maritime transportation policy, the different systems, functions, and targets of cabotage act have been analyzed. The innumerable factors affecting the Indonesia cabotage act which has had great impact on the regional economic growth has been studied and current methods and policies are being examined. Finally, the research paper evaluates the Indonesian Cabotage Act which is part of the transport and its impact on economic growth are summarized.